Metabolic Engineering of Carotenoid Biosynthesis in Escherichia coli by Ordered Gene Assembly in Bacillus subtilis - Nishizaki, Tomoko (American Society for Microbiology, 2007)
We attempted to optimize the production of zeaxanthin in Escherichia coli by reordering five biosynthetic genes in the natural carotenoid cluster of Pantoea ananatis. Newly designed operons for zeaxanthin production were constructed by the ordered gene assembly in Bacillus subtilis (OGAB) method, which can assemble multiple genes in one step using an intrinsic B. subtilis plasmid transformation system. The highest level of production of zeaxanthin in E. coli (820 μg/g [dry weight]) was observed in the transformant with a plasmid in which the gene order corresponds to the order of the zeaxanthin metabolic pathway (crtE-crtB-crtI-crtY-crtZ), among a series of plasmids with circularly permuted gene orders. Although two of five operons using intrinsic zeaxanthin promoters failed to assemble in B. subtilis, the full set of operons was obtained by repressing operon expression during OGAB assembly with a p(R) promoter-cI repressor system. This result suggests that repressing the expression of foreign genes in B. subtilis is important for their assembly by the OGAB method. For all tested operons, the abundance of mRNA decreased monotonically with the increasing distance of the gene from the promoter in E. coli, and this may influence the yield of zeaxanthin. Our results suggest that rearrangement of biosynthetic genes in the order of the metabolic pathway by the OGAB method could be a useful approach for metabolic engineering.